A method for measuring individual research productivity in hospitals: development and feasibility. Issue 1 (June 2015) - Caminiti, Caterina; Iezzi, Elisa; Ghetti, Caterina; De' Angelis, Gianluigi; Ferrari, Carlo
Abstract Background Research capacity is a prerequisite for any health care institution intending to provide high-quality care, yet, few clinicians engage in research, and their work is rarely recognized. To make research an institutional activity, it could be helpful to measure health care professionals' research performance. However, a comprehensive approach to do this is lacking. Methods We conducted a literature analysis to determine how best to assess research performance. Our method was not restricted to bibliometric and citation parameters, as is usually the case, but also including "hidden" activities, generally not considered in research performance evaluations. Results A set of 12 easily retrievable indicators was used and corresponding points assigned according to a weighting system intended to reflect the effort estimated to perform each activity. We observed a highly skewed score distribution, with a minority of health care professionals performing well across the indicators. The highest score was recorded for scientific papers (768/1098 points, 70 %). Twenty percent of researchers at our institution generated 50 % of points. Conclusions We develop a simple method for measuring research performance, which could be rapidly implemented in health care institutions. It is hoped that the proposed method might be useful for promoting research and guiding resource allocation, although further evaluations are needed to confirm the method's utility.